An Improved Run Length Encoding Scheme for Image Compression (International Journal of Engineering and Computer Science, 2017)
In this paper, we propose an Improved Run-Length Encoding (IRLE) scheme for image compression. Conventional RunLength Encoding is a widely used scheme as it is simple and effective but not suitable to represent non-block images. The IRLE which we have developed, combines runs and run values and it reduces the space required to store the image significantly. The compression ratio depends on the size and type of the input message. From the results obtained in this analysis, we conclude that the proposed approach is an efficient method for image compression and it provides high compression ratio and better compression percentage.